Análise do perfil epidemiológico, clínico e microbiológico das infecções de corrente sanguínea causadas por Candida spp. em pacientes oncológicos - Rodrigues, Beatriz Quental [UNIFESP] (2011)
Hematogenic infections by Candida species are important complications in oncology patients given their high mortality and morbidity. In different studies performed in general hospitals, cancer is the most prevalent disease for candidemia patients. Objectives: to assess the incidence, prognostic factors and epidemiological aspects of bloodstream infection by Candida spp in patients with solid tumors, comparing the epidemiological pattern of candidemia in surgical and non-surgical patients. Methods: retrospective observational study with systematic documentation of episodes of bloodstream infection by Candida spp. in patients with solid tumors admitted from March 2006 to December 2008 in two Brazilian cancer hospitals. Results: One hundred cases of candidemia in patients with solid tumors were analyzed. The incidence rates were 2.81 to 3.87 per 1000 hospital admissions. Surgery was performed in 53% of the patients. Candidemia was more prevalent in patients with gastrointestinal tract cancer (19%), gynecological (18%), head and neck (14%) and mama cancer (10%). The most prevalent malignancies in surgical patients were colon, rectum and anus (22.6%) and gynecological (30.2%), while for non-surgical patients the most prevalent were breast (17%) and head and neck cancer (19.1%). The clinical presentation of candidemia was as severe sepsis and septic shock in 44.7% of cases. Candidemia occurred in patients exposed to the risk factors classically described, specially the use of central venous catheter, broad spectrum antimicrobials and H2 blockers. Using urinary catheter and parenteral nutrition were more frequent in surgical patients, whereas in non-surgical patients the presence of neutropenia and mucositis, the use of corticosteroids and chemotherapy were more frequent. Candida albicans, C. parapsilosis and C. tropicalis. were the most prevalent species. Global mortality in 30 days was 45%. Factors related to worse prognosis were the use of corticosteroids and hospitalization in ICU. Although there was no significant difference in mortality among non-surgical and surgical patients, in the first group classification of severe sepsis or septic shock, central venous catheter use and maintaining the catheter were related to worst prognosis. Conclusions: Candidemia in adult patients with solid malignancies occurred more frequently in tumors of the gastrointestinal and gynecological tract, in patients with severe clinical illness and in patients exposed to the classical risk factors for candidemia. There was a predominance of Candida albicans, Candida parapsilosis and Candida tropicalis. The use of corticosteroids and hospitalization in ICU were related to worse prognosis.